ANALISIS IKON BAHASA DALAM LOGO OBJEK PEMAJUAN KEBUDAYAAN KOTA BANDUNG - Sella Sabrina Matin; Widianto Satrio Aji; Martien Roos Nagara (Jurusan Seni Rupa ISBI Bandung, 2024)
Language is one of the key aspects of human life that plays a vital role in communication and social interaction. An in-depth study of the structure and function of language is important for understanding the complex dynamics in society. This research aims to explore and analyze the Language Icons in the Logos of Bandung City Cultural Advancement Objects. This research adopts a qualitative descriptive method involving researchers who use themselves as the main tool to examine the condition of natural objects. Data collection involves triangulation, which is the integration of many methodologies. The Bandung College of Technology student team has collaborated with the Bandung City Culture and Tourism Office in designing 10+1 OPK logos and icons in accordance with Law No. 5 of 2017 concerning Cultural Advancement, as an effort to preserve and maintain Bandung city culture in accordance with city regional regulations Bandung Number 7 of 2023. It is hoped that the design of the OPK Logo and Icon will make it easier for the public to understand and study all forms of culture in the city of Bandung. Keywords: Logo, Icon, Language ——————————————————————— Bahasa merupakan salah satu aspek kunci dalam kehidupan manusia yang memainkan peran vital dalam komunikasi dan interaksi sosial. Pengkajian mendalam terhadap struktur dan fungsi bahasa menjadi penting untuk memahami dinamika kompleks dalam masyarakat. Penelitian ini bertujuan untuk menjelajahi dan menganalisis Ikon Bahasa dalam Logo Objek Pemajuan Kebudayaan Kota Bandung. Penelitian ini mengadopsi metode deskriptif kualitatif dengan melibatkan peneliti yang menggunakan dirinya sendiri sebagai alat utama untuk memeriksa keadaan benda alam. Pengumpulan data melibatkan triangulasi, yang merupakan integrasi dari banyak metodologi. Tim mahasiswa sekolah Tinggi Teknologi Bandung telah bekerja sama dengan Dinas Kebudayaan dan Pariwisata Kota Bandung dalam merancang 10+1 logo dan Ikon OPK sesuai dengan UU No.5 tahun 2017 tentang Pemajuan kebudayaan, sebagai upaya melestarikan dan menjaga kebudayaan kota Bandung sesuai dengan peraturan daerah kota Bandung Nomor 7 Tahun 2023 diharapkan perancangan Logo dan Ikon OPK ini dapat mempermudah masyarakat untuk lebih mudah memahami serta mempelajari segala bentuk kebudayaan kota Bandung. Kata Kunci: Logo, Ikon, Bahasa